Analysis of the Influence of Digital Training, Organizational Agility, and Digital Literacy on the Digital Resilience of Employees in the Public Service Sector - Djunaedi Djunaedi; Faisal Abubakar; Mohammad Azharie Hamdany; Sonya Sidjabat; Santrio Kamaluddin; Jumianis Yanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study seeks to explore the influence of digital training, organizational agility, and digital literacy on the digital resilience of employees within the public service sector. The study employs a quantitative approach through a survey distributed to 180 purposively sampled participants. A five-point Likert scale questionnaire, validated through the t-test and whose reliability was assessed using Cronbach’s Alpha, was used as the research instrument. Furthermore, the data underwent classical assumption tests that consist of normality, heteroscedasticity, and multicollinearity tests. Multiple linear regression was used for data analysis to explore the simultaneous and partial effects of the variables. Findings indicated that all three independent variables had a positive and statistically significant impact on digital resilience. In particular, the individual effects of digital training, organizational agility, and digital literacy were illustrated as being connectivity to employees' adaptive, psychological and technological capabilities in dealing with digital changes in the workplace. This study has the potential to significantly contribute to the literature on digital-based HR management through its theoretical implications as well as offering practical benefits to the public sector in terms of developing resilient human resources who are capable of coping with and staying up to date with the continuous digital transformation.